SOSIALISASI PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) OLEH GURU DI SDN 05 PONTIANAK TIMUR - Esterina, Esterina; Imran, Imran; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis thesis research titled socialization application of clean and healthy living behavior by a teacher at the State Elementary School 05 of East Pontianak.The problem in this research is how socialization application of clean and healthy life behavior on state elementary school 05 coastline?.Based on the formulation of the problem is formulated as a problem of the subcategories, namely: 1)what form of repressive socialization application of healthy life behavior in students of State Elementary School 05 of East Pontianak? . 2) How the application of participatory forms of socialization of healthy life behavior in students of State Elementary School 05 of East Pontianak ?This research using qualitative methods with the descriptive approach. Data collection tools used are interviews, observation and study of documentation. The results showed that the form of repressive socialization which is used by the State Elementary School 05, namely by giving direct punishment by teachers without giving non verbal actions. Participatory forms of socializing done State Elementary School 05, on when students have been applyingapplication of clean and healthy life behavior they were not given the gift material butÂ  the form of praise. eywords:application of clean and healthy life behavior, socialization